Proceso de atención de enfermería aplicado en paciente con leiomioma del útero perteneciente al hospital de Guayaquil “Dr Albert Gilbert” - Mollocana Sacoto, Katia Michelle (2018)
The leiomyomas or uterine fibroids are solid, benign tumors of the uterine muscle (matrix), which have variable shapes, locations and sizes that affect the uterine body. They are classified according to the location where they are located, they can be: intramural, submucosal and subserosal. The incidence of uterine myomatosis in Ecuador is estimated to be between 30% to 50% of women and this percentage increases up to 70% in women of childbearing age. The following case study deals with a 41-year-old patient admitted for presenting a clinical picture of vaginal bleeding in an abundant amount with the presence of clots plus abdominal pain of 48 hours of evolution, which is why she is hospitalized. Blood tests and transvaginal ultrasound are performed, the latter confirming the presence of leiomyoma located in the uterus. The treatment that will be applied is hysterectomy The general objective will be to provide quality nursing care by applying the Nursing Care Process in a 41-year-old patient with leiomyoma of the uterus, at the Guayaquil Hospital "Dr. Albert Gilbert '', to improve his health problem. For the realization of the clinical case we can mention that this disease is a real and potential problem in women over 35 years that can affect not only their quality of life but also emotionally. This research work allowed me to acquire new knowledge about this disease and about the appropriate and necessary nursing care that should be provided; and through the application of the nursing care process obtain the prompt recovery of the patient based on their treatment.